ANALISIS EFEKTIVITAS BIAYA METODE KB DAN KUALITAS HIDUP AKSEPTOR DI PUSKESMAS LOA JANAN - Yanti, Wiwid Verri; Warnida, Husnul; Sentat, Triswanto (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Family Planning (KB) is a national scale program to reduce birth rates and control population growth in Indonesia. Family planning has three phases. The first phase is the phase of delaying/preventing pregnancy. The second is the phase of spacing out pregnancies, and the third is the phase of terminating/terminating pregnancy/fertility. The use of contraceptives in family planning is an effort to prevent pregnancy. The most common contraceptive methods are the pill, injection, and IUD. The purpose of this study was to determine the cost-effectiveness of the use of oral contraceptive pills, contraceptive injections, and IUD at the Loa Janan Health Center. This study used a sample of 42 acceptors. The average cost of injection contraceptives is (Rp 25,000), pills (Rp 15,000), IUD (Rp 107,000) and the effectiveness of injection contraceptives (0.95%), pills (0.857%), and IUDs (0.867%). The ACER (Average cost-effectiveness ratio) value of injection contraceptives was Rp. 26,315, and 75% of the acceptors had an average quality of life. The ACER value of the pill was Rp. 17,502, and 85.7% of the acceptors had a good quality of life, the ACER value of the IUD was Rp. 123,414, and 60% of the acceptors had a good quality of life. The Pill-Injection's ICER (incremental cost-effectiveness ratio) value is Rp. 107,526. The ICER of IUD-Injection is Rp. -987,951, and the IUD-Pill (Rp.9,200,000). Hence, oral contraceptive gave a good quality of life and is more cost-effective than contraceptive injection and IUDs. Keywords: Cost-Effectiveness Analysis, IUD, injection contraceptive, oral contraceptive, Loa Janan Health Center